Description of Iron Status In Chronic Kidney Disease (CKD) Stadium 5 with Regular Hemodialization at the Hemodialysis Installation of Dustira Hospital - Tara Titian Maulidya, Daniel Setiawan Nathan, Endah Tri Widanarti, Eddy Harjadi Soenarso, Anita Liliana, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The number of patients with chronic kidney failure in Indonesia continues to increase and is estimated to grow by around 10% every year. Decreased of haemoglobin (Hb) in patients with CKD almost occurs in 80% of cases. Aim: The purpose of this study was to describe the iron status of patients with chronic kidney disease stage 5 undergoing regular hemodialysis. Methods: The study conducted is a descriptive study with a cross-sectional design to describe the iron status of stage 5 CKD patients undergoing regular hemodialysis at the Hemodialysis Installation of the Dustira Cimahi Hospital. Data used are secondary data from the medical records of stage CKD patients. 5 at the Hemodialysis Installation. Univariate analysis is performed by presenting data in terms of frequency and percentage or mean and standard deviation. Result: Patients in this study had a mean age of 46.75 years, a median age of 45 years (range: 18-71 years), and as many as 28 people were in the 37-45 year age group (range: 18-71 years) who underwent regular hemodialysis (35.0 percent ). The majority of CKD stage 5 patients who had regular hemodialysis were female, with as many as 44 out of 80 patients being female (55.0 percent ). In this study, 80 patients with CKD stage 5 were found to have decreased serum iron (66.3%) with a normal value range of 65-165 g/dl, TIBC decreased (43.8%) with a normal value range of 300 -360 g/dl, and transferrin saturation decreased (50%) with a normal range of 20-50%. Based on the serum iron, patients with CKD stage 5 who underwent regular hemodialysis had a mean serum iron of 56.53 g/dl)] and most of them had decreased serum iron, as many as 53 people out of 80 people (66.3%). Conclusion: The percentage of patients with chronic kidney disease stage 5 who underwent regular hemodialysis who experienced iron deficiency was 11.0% and did not have iron deficiency was 89.0%. The mean serum Fe, TIBC and TSAT levels of patients with chronic kidney disease stage 5 undergoing regular hemodialysis were 56.53 g/dL, 277.64, g/dL, and 23.10%, respectively.